Epidemiology with real-world data: deep endometriosis in women of reproductive age - Nilson Abrão Szylit; Luciana Cristina Pasquini Raiza; Anucha Andrade Schindler Leal; Sérgio Podgaec (Einstein (São Paulo))
ABSTRACT Objective: Endometriosis is characterized by the presence of glandular tissue or endometrial stroma outside the uterus. This study aimed to determine the prevalence of symptomatic deep endometriosis and the clinical factors associated with this condition in women of reproductive age. Methods: A descriptive prevalence study combined with a cross-sectional observational study was conducted between 2017 and 2021 at a public primary care outpatient clinic in Brazil. Women of reproductive age with at least one of the following symptoms were included in the study: deep dyspareunia, dysmenorrhea, chronic pelvic pain, intestinal or urinary symptoms during the menstrual cycle, or infertility. A sample size calculation indicated that an estimated sample of 269 patients was required for the study. Qualitative variables are described as absolute and relative frequencies, while quantitative variables are expressed as medians and quartiles. Factors associated with endometriosis were analyzed using logistic regression and multiple models. Results: Data from 1,445 patients were considered. Among these, 92 were diagnosed with deep endometriosis, resulting in a prevalence of 6.4% (95%CI= 5.2-7.7) and 34.2% among women with pelvic pain (95%CI= 28.8-40.1). Women with palpable posterior cul-de-sac nodules (0R= 3.58, 95%CI= 1.68-7.63, p = 0.001) or a retroverted uterus (0R= 2.36, 95%CI= 1.28-4.37, p = 0.006) were more likely to have endometriosis. Conclusion: Using real-world data, the prevalence of deep endometriosis was found to be 6.4% in women of reproductive age and 34.2% in those with pelvic pain. The primary clinical variables associated with endometriosis are palpable posterior cul-de-sac nodules and a retroverted uterus.